2021
DOI: 10.12800/ccd.v16i47.1673
|View full text |Cite
|
Sign up to set email alerts
|

Dual career of junior athletes: Identifying challenges, available resources, and roles of social support providers (Carrera dual de deportistas junior: identificando retos, recursos disponibles, y roles de apoyo social)

Abstract: Balancing between two different commitments, sport and education, has been demonstrated as one of the significant challenges for dual career athletes, namely student athletes. Since EU guidelines on dual careers of athletes was published, a number of studies have been conducted on the topic of dual careers. One of the Erasmus+ Sport projects, Dual Career for Junior Athletes (DCJA), has been designed to identify three main aspects regarding the dual career of junior athletes, aged between 15 and 19-year-old: th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…Coherently, in the present study assistance and tutorship for student-athletes has been most regarded as relevant and implementable service at HEI level. These findings substantiate the crucial role of tutors and counsellors with a thorough understanding of dual career challenges and opportunities as valuable supporters of the academic success of student-athletes [ 7 – 9 , 23 , 25 , 41 , 42 ]. In general, respondents declared that dual career tutorship/mentorship is the only service offered at their HEIs.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Coherently, in the present study assistance and tutorship for student-athletes has been most regarded as relevant and implementable service at HEI level. These findings substantiate the crucial role of tutors and counsellors with a thorough understanding of dual career challenges and opportunities as valuable supporters of the academic success of student-athletes [ 7 – 9 , 23 , 25 , 41 , 42 ]. In general, respondents declared that dual career tutorship/mentorship is the only service offered at their HEIs.…”
Section: Discussionsupporting
confidence: 62%
“…On the other hand, Storm et al [ 22 ] identified ten essential features of European dual career development environments which can help researchers and practitioners to optimize those environments for student-athletes. Furthermore, in a recent analysis by Hong et al [ 23 ] aiming to identify support/services for junior athletes, financial support emerged as the most prevalent type of support. In contrast, other types such as tutoring, academic flexibility, support from sports psychologists, nutritionists, strength and conditioning coaches, and dual career management were furnished in different combinations.…”
Section: Introductionmentioning
confidence: 99%
“…This project specifically targets young athletes aged 15-19 and aims to identify barriers, challenges, resources and skills related to their dual careers. The project also examines the roles and perspectives of the support staff of these student-athletes (7).…”
mentioning
confidence: 99%